Control of Polymer Phase Separation by Roughness Transfer Printing for 2D Microlens Arrays. Issue 28 (2nd June 2016) - Zhang, Xinyue; Gao, Naiwei; He, Yonglin; Liao, Shenglong; Zhang, Shiming; Wang, Yapei
Abstract : Great efforts have been devoted to the control of phase separation between blended polymers in terms of the advantages for engineering functional topologies. A simple and straightforward pathway through roughness transfer printing (RTP) is proposed to realize the control of polymer phase separation. The additional roughness difference, which is introduced by trace agarose transferred from a hydrogel stamp, offers a great effect on the rate of nucleation and coalescence orientation of polymethylmethacrylate (PMMA) protrusions grown from a polydimethylsiloxane (PDMS) network. Using a particular topography of agarose stamp and a proper growth time in toluene atmosphere, a 2D microlens array with high uniformity is obtained that shows great potential for optical applications. Moreover, the control of polymer phase separation was successfully extended to the collection and identification of fingerprints with a high degree of replication. Abstract : Control over the phase separation between two blended polymers leads to microlenses with a high degree of uniformity. In addition to the successful fabrication of an ordered microlens array for optical application, this technique can also be used in particular for fingerprint lifting. The features of a fingerprint can be successfully replicated and identified with the combination of transfer printing and phase separation.